The mysterious human heart. 1, Endlessly beating [videorecording (DVD)] - Jennings, Tom (Ambrose Video, 2007)
Each of the three programs that make up "The mysterious human heart focuses on a different aspect of what we thought we knew, what we know now, and what we're on the verge of learning about the heart. This material is presented through the real-life dramas of people who suddenly learn that a normal, functioning heart is not something that can be taken for granted. In Episode 1. we examine the heart as a muscle - pumping more than 100,000 times a day, pushing approximately five quarts of blood on an endless path delivering oxygen to every cell in the human body. This hour tells the story of the normal heart through the histories of three people with end-stage heart failure, where a pump may be a temporary remedy, but in the long term, a transplant is often a necessity.